Chemical Considerations for an Updated National Assessment of Brackish Groundwater Resources. Issue 4 (27th August 2015) - McMahon, P.B.; Böhlke, J.K.; Dahm, K.G.; Parkhurst, D.L.; Anning, D.W.; Stanton, J.S.
Abstract: Brackish groundwater (BGW) is increasingly used for water supplies where fresh water is scarce, but the distribution and availability of such resources have not been characterized at the national scale in the United States since the 1960s. Apart from its distribution and accessibility, BGW usability is a function of the chemical requirements of the intended use, chemical characteristics of the resource, and treatment options to make the resource compatible with the use. Here, we discuss relations between these three chemical factors using national‐scale examples and local case studies. In a preliminary compilation of BGW data in the United States, five water types accounted for the major‐ion composition of 70% of samples. PHREEQC calculations indicate that 57–77% of samples were oversaturated with respect to barite, calcite, or chalcedony. In the study, 5–14% of samples had concentrations of arsenic, fluoride, nitrate, or uranium that exceeded drinking‐water standards. In case studies of the potential use of BGW for drinking water, irrigation, and hydraulic fracturing, PHREEQC simulations of a hypothetical treatment process resembling reverse osmosis (RO) showed that BGW had the potential to form various assemblages of mineral deposits (scale) during treatment that could adversely affect RO membranes. Speciation calculations showed that most boron in the irrigation example occurred as boric acid, which has relatively low removal efficiency by RO. Results of this preliminary study indicate that effective national or regional assessments of BGW resources should include geochemical characterizations that are guided in part by specific use and treatment requirements.